PENGARUH INTERNET BANKING TERHADAP KINERJA KEUANGAN PADA BANK UMUM KONVENSIONAL YANG TERDAFTAR DI BURSA EFEK INDONESIA (PERIODE 2015 – 2018) - Yohani Yohani; Frida Inggrit Dita (Neraca, 2019)
One way to see the development of the company by looking at the performance achieved by the company. In the era of Industry 4.0 it is inseparable from the role of IT, especially to facilitate customer needs and industrial competition, including the banking industry, which now involves internet banking. This study aims to examine the effect of variable Internet Banking on Financial Performance. The sampling technique used was purposive sampling with the criteria of conventional commercial banks in Indonesia that presented financial statements for the period 2015 to 2018, so that the samples used were 11 companies listed on the Indonesia Stock Exchange. The analysis technique used is linear regression. Before carrying out the hypothesis test, statistically and the normality test carried out was fulfilled. Then testing the hypothesis using the t test results showed that internet banking had no significant effect on financial performance. The non-effect of internet banking in Conventional Commercial Banks is influenced by the internet banking needs that cannot be left behind by the banking world, especially Conventional Bank.